2004
DOI: 10.21273/hortsci.39.5.1070
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Quality Indices in Eight Nance [Byrsonima crassifolia (L.) H.B.K.] Selections

Abstract: Nance [Byrsonima crassifolia (L.) HBK.] is a tropical fruit cultivated along the coastal areas of Mexico. Nance consumption has increased due to its versatility, as it can be used as fresh fruit, refreshments, and alcoholic beverages and also for preparing fruit rolls, bottled drinks, jellies, syrup, ice cream, and cakes. However, the broad variation in fruit quality parameters, like juice acidity, total soluble solids, skin color, and size, seems to limit its use. Since frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…For instance, Bactrocera carambolae, the carambola fruit fly, is a B. crassifolia pest (Jesus-Barroos et al, 2015). However, no phytosanitary problems related to B. crassifolia have been generated so far, probably due to natural control by parasitoids and predators (Medina-Torres et al, 2013). It should be noted that interactions of up to 32 species of mites have been reported in nanche leaves, some of which are predators (Da Silva Noronha et al, 2020) that could be a reference for designing biological control strategies in B. crassifolia.…”
Section: Pests and Diseasesmentioning
confidence: 99%
“…For instance, Bactrocera carambolae, the carambola fruit fly, is a B. crassifolia pest (Jesus-Barroos et al, 2015). However, no phytosanitary problems related to B. crassifolia have been generated so far, probably due to natural control by parasitoids and predators (Medina-Torres et al, 2013). It should be noted that interactions of up to 32 species of mites have been reported in nanche leaves, some of which are predators (Da Silva Noronha et al, 2020) that could be a reference for designing biological control strategies in B. crassifolia.…”
Section: Pests and Diseasesmentioning
confidence: 99%
“…Acidity is a key eating quality criteria of fruit fresh-cuts which plays its role in relation to sugar content. The ratio of TSS/TA is used as a quality index for some horticultural products (Medina-Torres et al, 2004). As presented in Figure 4b, changes in TSS values were significant only for control samples (1.8% in 7 days), while the variation of TSS for other treatments were ranged between 0 and 0.8%.…”
Section: Titratable Acidity (Ta) and Tssmentioning
confidence: 99%
“…Nance has different names in America: nanchi, nananché and nantzin in Mexico; nancito or crabo in Honduras; craboo and crapoo in Belice; doncella and maricao in Dominican Republic; maricao cimarrón verde and peralejo in Puerto Rico; perelejo de sabana in Cuba; tapal in Guatemala; chaparro de chinche or sabana, manteco in Venezuela; murici and mirixi in Brazil (Morton, 1987;Santos, 2013). Nance fruits are consumed on a seasonal basis (SIAP, 2015) and are produced in the wild as well as in small orchards and sold in local markets as a fresh fruit or in the form of jam, liquor and jelly on a retail basis during the production season (Medina-Torres et al, 2004;Duarte, 2011;Santos, 2013). The total production in Mexico reached 31,180.11 tons in 201531,180.11 tons in (SIAP, 2015 and it has been reported that this fruit is an important source of ascorbic acid, phenolic compounds (Caballero-Roque et al, 2012), and other phytochemicals such as carotenoids as lutein and zeaxanthins (Mariutti et al, 2014;Irías-Mata et al, 2015).…”
Section: Introductionmentioning
confidence: 99%